POLA KONSUMSI DAN PERMINTAAN BERAS TINGKAT RUMAH TANGGA DI KOTA BANDAR LAMPUNG - Ican Aido; Fembriarti Erry Prasmatiwi; Rabiatul Adawiyah (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2021)
This research aims to examine the pattern of rice consumption, rice demand and the factors that influence household rice demand in Bandar Lampung City.  This study used a survey method involving 64 respondents chosen randomly and consisted of 32 respondents from Panjang District and 32 respondents from by Sukarame District.  Data collection was carried out in November to December 2018 and analyzed qualitatively, statistically descriptive and verification using multiple linear regression. The results showed that the pattern of household rice consumption in Bandar Lampung City consisted of the types of rice consumed by households was random rice, IR 64, Pandan Wangi, and Rojolele with the type of rice most consumed by households was IR 64. The quality of rice consumed by households was super rice.  Most of the households consume rice because of habits.  Total household rice consumption was 15-25 kg per month.  The majority of households consume 3 times per day. The total household rice demand in Bandar Lampung City was 25.31 kg per month and the average demand per capita was 6.33 kg per month.  Factors affecting household rice demand in Bandar Lampung City were the price of bread, the price of chicken, and the number of household members.Key words: consumption pattern, demand, rice